Performance of a diagnostic algorithm based on a prediction rule, D-dimer and CT-scan for pulmonary embolism in patients with previous venous thromboembolism - Valls, Maria José Fabiá; Hulle, Tom van der; den Exter, Paul L.; Mos, Inge C. M.; Huisman, Menno V.; Klok, Frederikus A. (Thrombosis and Haemostasis, 2015)
Diagnostic management of suspected pulmonary embolism (PE) in patients with a history of venous thromboembolism (VTE) is complicateddue to persistent abnormal D-dimer levels, residual embolic obstruction and higher clinical prediction rule (CPR) scores. We aimed to evaluate the safety and efficiency of the standard diagnostic algorithm consisting of a CPR, D-dimer test and computed tomography pulmonary angiography (CTPA) in this specific patient category. We performed a systematic literature search for prospective studies evaluating a diagnostic algorithm in consecutive patients with clinically suspected PE and a history of VTE. The VTE incidence rates during three-month follow-up and the number of indicated CTPAs were pooled using random effect models. Four studies concerning 1,286 patients were included with a pooled baseline PE prevalence of 36 % (95 % confidence interval [CI] 30–42). In only 217 patients (15 %; 95 %CI 11–20) PE could be excluded without CTPA. The three-month VTE incidence rate was 0.8 % (95 %CI 0.06–2.4) in patients managed without CTPA, 1.6 % (95 %CI 0.3–4.0) in patients in whom PE was excluded by CTPA and 1.4 % (95 %CI 0.6–2.7) overall. In the pooled studies, PE was safely excluded in patients with a history of VTE based on a CPR followed by a D-dimer test and/or CTPA, although the efficiency of the algorithm is relatively low compared to patients without a history of VTE.
Keywords: Pulmonary embolism; diagnosis; D-dimer; multidetector computed tomography; safety; meta-analysis